Bureaucracy and bribery: a conceptual framework - Berkman, Omit
Public bureaucracies carry a potential for bribery. This paper tries to identify and examine the factors affecting the potential or the probability of bribery. It is argued that the specific nature and the probability of bribery depend on the persons involved, the corrupt act in question, the organization in which the event takes place and finally the socio-cultural, economic and political environment within which the organization operates. - Reproduced
Keywords: Corruption; Bribery; Bureaucracy